2013
DOI: 10.1245/s10434-013-3130-3
|View full text |Cite
|
Sign up to set email alerts
|

Race Does Not Impact Pancreatic Cancer Treatment and Survival in an Equal Access Federal Health Care System

Abstract: We observed no disparities in either management or survival between white and black patients with PDAC treated in the DoD's equal access health care system. These data suggest that improving the access of minorities with PDAC to health care may reduce disparities in their oncologic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
3
24
1
Order By: Relevance
“…2 Importantly, in this cohort, there was no difference in the rates of chemotherapy utilization between black and white patients, contrary to that reported in other studies. 34 Additionally, black patients tended to be younger than whites at the time of diagnosis, but there was no difference in baseline tumor stage or site of distant disease.…”
Section: To the Editorcontrasting
confidence: 92%
“…2 Importantly, in this cohort, there was no difference in the rates of chemotherapy utilization between black and white patients, contrary to that reported in other studies. 34 Additionally, black patients tended to be younger than whites at the time of diagnosis, but there was no difference in baseline tumor stage or site of distant disease.…”
Section: To the Editorcontrasting
confidence: 92%
“…Previous studies have demonstrated poorer QOL in non-white cancer patients [31][32][33] but limited literature exists on racial disparities in long-term survivors of cancer surgery [34]. The reasons behind the associations found in our study are unclear but may be related to differences in conceptualization or expectations of surgery, disparities in quality of care or access to services [35], or differences in coping, adjustment, or adaptation skills. Differences in comorbidities, short and long term postoperative complications, socioeconomic status, education, language, and/or acculturation may also influence outcomes.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 54%
“…In one study, the HR of mortality reached 0.368 in patients treated with chemotherapy compared with those who did not receive chemotherapy ( Asari et al, 2016 ). Conversely, some studies failed to find an association between chemotherapy and OS in pancreatic cancer ( Chen et al, 2015 ; Kanda et al, 2014 ), whereas others reported a negative impact of chemotherapy on the survival of pancreatic cancer ( Bergquist et al, 2016 ; Lee et al, 2013 ). In the present study, chemotherapy was a good prognostic factor for OS in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%